2020
DOI: 10.1111/vsu.13445
|View full text |Cite
|
Sign up to set email alerts
|

Use of bilateral superficial gluteal muscle flaps for the repair of ventral perineal hernia in dogs: A cadaveric study and short case series

Abstract: Objective: To describe bilateral mobilization of the superficial gluteal muscle (SGM) to treat ventral perineal hernias in dogs. Study design: Cadaveric study and short case series. Sample population: Male dog cadavers (n = 10) weighing between 5 and 42 kg and three dogs treated for ventral perineal hernia. Methods: Cadavers were positioned in right and left lateral recumbency to free the origin and insertion of the ipsilateral SGM except for muscle fibers originating on the first tail vertebra and sacrotubero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This study has several limitations. The low number of cases reported and the retrospective nature of the study make significant conclusions difficult; however, in terms of outcome, our results are similar to the Bernardé et al (2018) or Bitton et al (2020) who reported a 93 and 100% of resolution of the clinical signs, respectively. Our short-term wound related complication rate was slightly higher than studies with a linear/curved incision and further investigation is required to determine whether changing the skin incision will improve the technique.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…This study has several limitations. The low number of cases reported and the retrospective nature of the study make significant conclusions difficult; however, in terms of outcome, our results are similar to the Bernardé et al (2018) or Bitton et al (2020) who reported a 93 and 100% of resolution of the clinical signs, respectively. Our short-term wound related complication rate was slightly higher than studies with a linear/curved incision and further investigation is required to determine whether changing the skin incision will improve the technique.…”
Section: Discussionsupporting
confidence: 48%
“…(2018) or Bitton et al . (2020) who reported a 93 and 100% of resolution of the clinical signs, respectively. Our short‐term wound related complication rate was slightly higher than studies with a linear/curved incision and further investigation is required to determine whether changing the skin incision will improve the technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations